Electronic band dispersion determination in azimuthally disordered transition-metal dichalcogenide monolayers - Park, S.; Schultz, T.; Han, A.; Aljarb, A.; Xu, X.; Beyer, P.; Opitz, A.; Ovsyannikov, R.; Li, L-J; Meissner, M.; Yamaguchi, T.; Kera, S.; et al. (NATURE PUBLISHING GROUP, 2019)
Generally, the lack of long-range order in materials prevents from experimentally addressing their electronic band dispersion by angle-resolved photoelectron spectroscopy (ARPES), limiting such assessment to single crystalline samples. Here we demonstrate that the ARPES spectra of azimuthally disordered transition metal dichalcogenide (TMDC) monolayers with 2 H phase are dominated by their band dispersion along the two high symmetry directions Gamma-K and Gamma-M. We exemplify this by analyzing the ARPES spectra of four prototypical TMDCs within a mathematical framework, which allows to consistently explain the reported observations. A robust base for investigating TMDC monolayers significantly beyond single crystal samples is thus established.
Keywords: TOTAL-ENERGY CALCULATIONS; GRAIN-BOUNDARIES; HETEROSTRUCTURES; GENERATION; GROWTH